Administration of immunobiotic Lactobacillus plantarum delays but does not prevent lethal pneumovirus infection in Rag1−/− mice. Issue 3 (15th June 2017) - Percopo, Caroline M.; Ma, Michelle; Rosenberg, Helene F.
Abstract : L. plantarum at the respiratory mucosa mediates cross‐protection against lethal virus‐induced inflammation, but does not sustain survival in the absence of endogenous virus clearance mechanisms. Abstract : Administration of immunobiotic Lactobacillus plantarum (Lp) directly to the respiratory mucosa promotes cross‐protection against lethal pneumovirus infection via B‐cell‐independent mechanisms. In this study, we examined Lp‐mediated cross protection in Rag1 −/− mice which cannot clear virus from lung tissue. Although Lp was initially protective, Rag1 −/− mice ultimately succumbed to a delayed lethal outcome associated with local production of the proinflammatory cytokines CCL1, ‐2, and ‐7, granulocyte recruitment, and ongoing virus replication. By contrast, CD8 null mice, which are fully capable of clearing virus, are protected by Lp with no delayed lethal outcome, granulocyte recruitment to the airways, or induction of CCL7. Repeated administration of Lp to virus‐infected Rag1 −/− mice had no impact on delayed mortality. Moreover, administration of Lp to the respiratory mucosa resulted in no induction of IFN‐α or ‐β in Rag1 −/− or wild‐type mice, and IFN ‐ab R gene deletion had no impact on Lp‐mediated protection. Overall, our findings indicate that although Lp administered to the respiratory tract has substantial impact on lethal virus‐induced inflammation in situ, endogenous virus clearance mechanisms are needed to promote sustained protection. Our results suggest that a larger understanding of the mechanisms and mediators that limit acute virus‐induced inflammation may yield new and useful therapeutic modalities.